2013
DOI: 10.4103/0019-5413.118201
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of unicompartmental knee arthroplasty in octogenarians with tricompartmental osteoarthritis: A longer followup of previously published report

Abstract: Background:Unicompartmental knee arthroplasty (UKA) has specific indications, producing excellent results. It, however, has a limited lifespan and needs eventual conversion to total knee arthroplasty (TKA). It is, therefore, a temporizing procedure in select active young patients with advanced unicompartmental osteoarthritis (UCOA). Being a less morbid procedure it is suggested as an alternative in the very elderly patients with tricompartmental osteoarthritis (TCOA). We performed UKA in a series of 45 octogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Because low-grade cartilage injuries do not have much influence on the long-term effects of UKA [ 19 21 ], as long as image examination can distinguish between low-grade and high-grade injuries, it can become a suitable decision aid for UKA. Our study showed that the accuracy and specificity of MRI were much higher than valgus stress radiograph.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because low-grade cartilage injuries do not have much influence on the long-term effects of UKA [ 19 21 ], as long as image examination can distinguish between low-grade and high-grade injuries, it can become a suitable decision aid for UKA. Our study showed that the accuracy and specificity of MRI were much higher than valgus stress radiograph.…”
Section: Discussionmentioning
confidence: 99%
“…Outerbridge grade [ 18 ] (Table 1 ) was the gold standard and was assessed by an experienced surgeon for intraoperative cartilage assessment. Slight cartilage injury of the lateral compartment did not affect the efficacy of UKA [ 19 21 ]. So, patients with Outerbridge grades 0–2 (non-high-grade injuries) underwent UKA, while patients with Outerbridge grades 3–4 (high-grade injuries) underwent TKA.…”
Section: Methodsmentioning
confidence: 99%